LOS SORDOS NO VAN AL CINE: LA ACCESIBILIDAD DE LAS PERSONAS CON DISCAPACIDAD AUDITIVA EN LAS SALAS DE CINE ESPAÑOLAS - Elisa MARTÍNEZ AMADOR, (Fonseca, Journal of Communication, 2023)
In Spain there is over a million people with hearing disability and their integration in information society is a challenge. Especially in the field of accessible cinema, where only three systems are available: the mobile application Whatscine, the magnetic loop system and subtitling screen that follows a color-coding to identify the characters and contextual information